Circulating Exosomal miRNAs as Biomarkers for the Diagnosis and Prognosis of Colorectal Cancer - Alves dos Santos, Katiusse (Int J Mol Sci, 2020)
Colorectal cancer (CRC) is one of the most common malignant tumors in the gastrointestinal tract. It is a multifactorial disease that involves environmental factors, genetic factors, and lifestyle factors. Due to the absence of specific and sensitive biomarkers, CRC patients are usually diagnosed at an advanced stage and consequently suffer from a low 5-year overall survival rate. Despite improvements in surgical resection and adjuvant chemotherapy, the prognosis of patients with CRC remains unfavorable due to local and distant metastases. Several studies have shown that small noncoding RNAs, such as microRNAs packed in exosomes, are potential biomarkers in various types of cancers, including CRC, and that they can be detected in a stable form in both serum and plasma. In this review, we report the potential of circulating exosomal miRNAs to act as biomarkers for the diagnosis and prognosis of CRC.